Acute Pyrethroids Insecticide Ingestion in An Elderly Patient - Yhan Batista; Novira Widajanti (Institute of Medico-legal Publications Pvt Ltd, 2021)
Insecticide ingestion is not an uncommon phenomenon found in daily practices. An elderly woman, 69-yearold,was rushed to emergency room due to household cleaning liquid ingestion. There was a history of previoussuicide attempt and severe depressive episode before. Since there was no sign of severe intoxication, patientreceived symptomatic treatment. Patient was discharged with symptomatic treatment and antidepressants.